Impact of common skin diseases on children in rural Côte d'Ivoire with leprosy and Buruli ulcer co-endemicity: A mixed methods study. - Rie Roselyne Yotsu; Colombe Coffie Comoé; Germaine Taïba Ainyakou; N'guessan Konan; Amari Akpa; Aubin Yao; Julien Aké; Bamba Vagamon; Rigobert Abbet Abbet; Roger Bedimo; Roderick Hay (Public Library of Science (PLoS), 2020)
BACKGROUND:Skin-related neglected tropical diseases (skin NTDs) occur against a background of a very high prevalence of common skin diseases in sub-Saharan Africa. In this study, we examined the knowledge, attitude and practices (KAP) and the impact of common skin diseases in children living in a leprosy and Buruli ulcer (BU) co-endemic district in a west African country of Côte d'Ivoire, in order to help inform disease control efforts for skin NTDs. METHODS AND PRINCIPLE FINDINGS:Fourteen focus group discussions (FGDs) with schoolchildren, 5 FGDs with parents of a child affected with skin disease(s), and 27 in-depth semi-structured interviews with key personnel were conducted. The Children's Dermatology Quality of Life Index (CDLQI) questionnaire was applied to 184 schoolchildren with skin diseases. We found that there was ignorance or neglect towards skin diseases in general, due to their high prevalence and also the perceived minimal impact on children's daily lives. While the median score for the CDLQI questionnaire was 5 (IQR 2-9) out of 30, a range of scores was observed. Symptoms such as pruritus and experiencing bullying by classmates contributed to reduction in their quality of life. Poor hygiene was considered as a major cause of skin diseases. CONCLUSIONS/SIGNIFICANCE:Despite their high impact on affected populations, we observed a high level of ignorance and neglect toward common skin diseases. There is a critical need to increase awareness of skin diseases, or skin health promotion, which supports changing of the health-seeking behaviour for skin conditions. This will aid in early detection and treatment of the skin NTDs, in addition to providing benefits for those affected by other skin diseases. Educational opportunities should be utilized to their utmost. One would be associated with water, sanitation, and hygiene (WASH) strategies, but careful messages need to be developed and delivered.